APPLYING THE SOFTWARE PACKAGE TABLE CURVE 2D FOR CALCULATING THE ENERGY REQUIRED FOR MELTING OF FROZEN BOUND WATER IN WOOD (Innovation in Woodworking Industry and Engineering design, 2026)
A mathematical description of the energy Qice-bw required for melting the temperature dependent part of frozen bound water in wood, using a software package Table Curve 2D v.5.01 has been presented. This package allows for the selection of equations, which provide the best similarity between the calculated with them values of Qice-bw during thermal treatment of wood containing ice and the respective numerical data obtained with an adequate temperature-energy model of Qice-bw. The type and coefficient values of the Table Curve equations for Qice-bw in this work have been determined for the case of thermal treatment of frozen beech wood with an initial temperature of −1oC, −10oC, −20oC, −30oC, −40oC and moisture content of 0.4 kg·kg-1, 0.6 kg·kg-1, 0.8 kg·kg-1. The equations obtained for Qice-bw can be used for development and automatic implementation of scientifically based energy-efficient regimes for steaming or boiling of frozen wood materials with different parameters.